THE FIRST POSITION OF THE DAYAK SOCIAL COMMUNITY AND THE EMPOWERMENT OF EMPOWERMENT IN THE CITY OF PALANGKA RAYA - Sumiatie (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2017)
This thesis study discusses two main issues namely: first, arrangement of position and authority of Damang in life of Dayak tribe society, and Second is about effort of empowering Damang in Palangka Raya city. The discussion until the conclusion in this thesis, can be described as follows: (1). The position of Damang is legally recognized in the prevailing laws and regulations and still adhered by Dayak society in Palangkaraya; (2). In the implementation of its function Damang as Head of Adat always put forward the ways of settling the case peacefully based on the principle of harmony, ie mutual tandem, mutual love, mutual care, so that can solve the problem thoroughly and the result can satisfy all parties; (3). In the present condition the role of Damang as head of adat ability to remain effective and not lose its function. Empowerment steps can be done internally and externally. Internally more on improving human resources and ways of resolving custom cases. Then externally more to the provision of facilities and infrastructure supporting the implementation of duties of Damang as head of adat.